Asouzu’s Complementarism and Nietzsche’s Perspectivism: Implications for Cross-Cultural Philosophizing - Ojimba, Anthony Chimankpam; Anichebe, Obiora (Global Journal of Cultural Studies, 2022)
This paper examines Asouzu’s complementarism and Nietzsche’s perspectivism with a view to showing how convergence and divergence of thoughts in the Asouzuan and Nietzschean philosophy contexts can inform cross-cultural philosophizing. Asouzu’s complementarism projects multiplicity of perspectives as constitutive of reality and construes it as a composite of missing links, while Nietzsche’s perspectivism also postulates multiplicity of views and interpretations as he believes that reality is deeply rooted in infinite possibilities. Attempts are made, in this paper, to articulate the essential principles of Asouzu’s complementarism and to highlight the dynamics of Nietzsche’s perspectivism in a fruitful encounter of the African tradition of thought which Asouzu belongs to and the European thought tradition which Nietzsche belongs to. These two traditions of thought will be critically x-rayed to show their implications for cross-cultural philosophizing. Simply put, the paper will show how the philosophical studies of the ideas of complementarism and perspectivism in the thoughts of the German philosopher, Friedrich Nietzsche, and the African philosopher, Innocent Asouzu, can enrich the cultural understanding of human societies and ideas for the betterment of universal values and humanism.